Development of a hot stamping clinching tool. (August 2018) - Chen, Li-Wei; Cai, Ming-Jhe
Abstract: A hot stamping clinching tool that integrates a forming system, a heating system and a cooling system is developed. A traditional heating furnace is replaced by resistance heating technology. DEFORM-3D is used to simulate the heating process, cooling efficiency and formability in the design stage. A series of experiments confirms the design of the tool. Results show that the tool structure accurately controls the movement of the electrode and the punch stroke. Experiments showed that the condition of the sheet's surface, the sheet's thickness and its size affect the resistance heating. If the contact surface between sheets is uneven, current flows through from the partial contact point, which results in non-uniform heating. If two layers of sheets of different thickness are heated at the same time, the thinner the sheet, the faster is the heating rate. An increase in the sheet's size results in a decrease in the heating rate. In terms of the connection strength, due to the high cooling rate in the present experimental, the tensile strength of the sheet at the clinching point is increased by 3 to 4 times. Resultant the elongation is reduced to less than 2% so the cracking point occurs around the clinching joint and not the joint point itself, during shear strength test. Therefore, it is important to control the cooling process to get better clinching joint condition.